Mapping Success and Failure Factors in Enterprise Resource Planning (ERP) Implementation: A Global Systematic Literature Review - Fika Halimah Balqis; Farah Adila; Muhammad Qomarul Huda; Rahajeng, Elsy (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study examines the essential reasons that determine the success and failure of Enterprise Resource Planning (ERP) implementation within international organizations. From a systematic review of thirteen peer-review articles between 2022 and 2025, the study identifies eight essential success factors, such as top management support, training of end-users, alignment of business processes, and technological readiness, and eight failure factors that are significant, among which, a lack of leadership involvement, resistance by end-users, and inefficient reengineering of processes. Another essential finding pertains to symmetry between the factors, such that exclusion of success components tends to lead to failure. The study incorporates current theoretical models such as TAM, TOE, and the IS Success Model to arrive at a systematic view of ERP dynamics. The study enriches research and practice by suggesting a holistic framework to guide strategy development, risk mitigation, and ERP implementation success within diverse business contexts.